The Role of Energy Taxation in Terms of Achieving Climate Neutrality - Lovas, Dóra (Review of European and Comparative Law, 2022)
The energy tax is a type of environmental tax. In addition to its ability to generate revenue for the central budget, it is important that it can have a major impact on the achievement of the European Union’s significant but not legally binding objectives in the field of energy policy and climate change. The role of the energy tax is gradually increasing, partly due to the growing importance of environmental considerations in certain policies, on the other hand, the EU attaches great importance to the harmonization of these tax rules, as almost 75% of environmental taxes in integration come from the energy sector, so the role of energy taxes in environmental taxation and policy is also important. The EU wants to reduce its greenhouse gas emissions by 55% by 2030 and achieve full climate neutrality by 2050, as set out in the Green Agreement Communication. Aiming to achieve these goals, the European Commission has adopted the so called ‘Fit for 55’ package of proposals on climate protection, which, in addition to several measures, states the need of the amendment of the Energy Tax Directive (hereinafter: Energy Tax Directive, the Directive). The reason for this is that, in its current form, it is not in line with climate protection goals, as it does not encourage the reduction of greenhouse gas emissions and energy efficiency.